Corruption and earnings management in developed and emerging countries - Lourenço, I. C.; Rathke, A.; Santana, V.; Branco, M. C. (Corporate Governance, 2018)
Purpose – The purpose of this study is to examine whether firms from countries presenting higher levels of corruption are more likely to have higher levels of earnings management than their counterparts from countries with lower levels of corruption. It also explicitly examines how this relationship compares between emerging and developed economies. Design/methodology/approach – Using multiple regression analysis, this study tests the hypothesis of positive association between the countries’ level of corruption and the level of earnings management using a sample of foreign firms with American Depositary Receipts (ADR) in the U.S. market. Findings – Findings indicate that higher corruption perception is related to higher incentives for firms to manipulate earnings in the case of emerging countries. Such results are not identified in developed countries where the level of minority investors’ protection is higher. Findings also indicate that in developed countries earnings management is negatively related to investor protection, which is not the case for emerging countries. Originality/value – As far as we are aware, our study is the first to examine the effects of corruption on earnings management on the basis of accounting firm level data.